2012
DOI: 10.1523/jneurosci.2911-11.2012
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of Catecholamine Systems during Induction of Long-Term Potentiation at Hippocampal CA1 Synapses in HPC-1/Syntaxin 1A Knock-out Mice

Abstract: The membrane protein HPC-1/syntaxin 1A is believed to play a key role in synaptic vesicle exocytosis, and it was recently suggested to be required for synaptic plasticity. Despite evidence for the function of HPC-1/syntaxin 1A in synaptic plasticity, the underlying cellular mechanism is unclear. We found that although fast synaptic transmission and long-term depression were unaffected, HPC-1/syntaxin 1A knock-out (STX1A Ϫ/Ϫ ) mice showed impaired long-term potentiation (LTP) in response to theta-burst stimulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 59 publications
1
23
1
Order By: Relevance
“…Using immunohistochemical labeling, we also showed a concordant increase in STX1A protein expression within the hippocampus of cKO animals. STX1A plays a central role in the docking of presynaptic vesicles via the formation of the SNARE complex and is required for normal hippocampal LTP (Bennett et al 1992;Mishima et al 2012). While STX1A is essential for voltagedependent calcium and potassium signaling (and thus for synaptic transmission), its overexpression inhibits exocytosis and blocking STX1A enhances Ca 2+ influx into cells via N-type calcium channels (Mitchell and Ryan 2005;Swayne et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Using immunohistochemical labeling, we also showed a concordant increase in STX1A protein expression within the hippocampus of cKO animals. STX1A plays a central role in the docking of presynaptic vesicles via the formation of the SNARE complex and is required for normal hippocampal LTP (Bennett et al 1992;Mishima et al 2012). While STX1A is essential for voltagedependent calcium and potassium signaling (and thus for synaptic transmission), its overexpression inhibits exocytosis and blocking STX1A enhances Ca 2+ influx into cells via N-type calcium channels (Mitchell and Ryan 2005;Swayne et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we reported that deletion of STX1A has no effect on evoked or spontaneous fast synaptic transmission, although impairments are seen in hippocampal monoaminergic transmission, long-term potentiation and learning ability [12], [13]. This phenotype might be due to compensation by STX1B, because these isoforms are highly homologous.…”
Section: Introductionmentioning
confidence: 89%
“…S2). However, unlike Stx1a −/− or Stx1a +/− (Mishima et al ., ), the elevation in monoamine concentrations following high K stimulation was not different between WT and Stx1b +/− mice. Interestingly, the DA concentration in the basal condition was higher in Stx1b +/− compared with WT mice, although the 5‐HT and NE concentrations in the basal condition were not different (Fig.…”
Section: Resultsmentioning
confidence: 99%